PENYEBAB KEMISKINAN MASYARAKAT TANI (Studi Di Dusun Ngebrong, Desa Tawangsari, Kecamatan Pujon, Kabupaten Malang) - Soesilo, Yohanes Hadi; Suman, Agus; Kaluge, David (Journal of Indonesian Applied Economics, 2008)
East Java Province was the first province with the largest amount of poor peoplein Indonesia. Irawan and Romdiati said that in their invention, 72% of the poorfamily depend their main income on the agricultural sector and most of them livein village area. This research has been done in Ngebrong Orchard, Tawangsarivillage Pujon Sub district, Malang Regency and used phenomenology approachin order to find the true reality which is hidden in human awareness that causedthe poverty. Some significant findings are found  in this research. Firstly, somecircumscription, such as geographical Isolation, lack of water resources – dependonly on climate and rainy season - has caused them suffer in poverty. Secondly,no monetary  and government  institution  care  their need  for a  non collateralcredit and assistance which will help them to leap from their condition. Thirdly,non clear  land working agreement makes  them have no  future  stable  incomeassurance. Fourthly,  cultural boundaries,  such as buwuh culture and  povertyhereditary culture make them more powerless. And the last, Fifthly, the acceptanceof their present life is a matter of being forced to submission, there is no other wayfor them to go rather than to accept it, and in fact it will help them happier.Keywords: Poverty, Farm Household, Suistainability